Pengaruh Permainan Edukatif Berbasis Powerpoint Terhadap Kemampuan Matematika Anak Usia 5-6 Tahun Di Raudhatul Athfal Al-Ikhlas Darma Wanita Kemenag Pasaman Barat - Ayu Pasmandari Putri; Zulminiati (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2025)
This study aims to see the effect of using powerpoint-based educational games on the math skills of children aged 5-6 years at Raudhatul Athfal Al-Ikhlas Darma Wanita Kemenag West Pasaman. This research is motivated by the learning methods used by teachers are less interesting with the lecture method and manual media so that children are less motivated to learn and children's math skills are still low. This study uses quantitative research with experimental research methods, namely the Quasi Experimental research design. The population of this study were all children in Raudhatul Athfal Al-Ikhlas Darma Wanita Kemenag West Pasaman as many as 44 and the sample was children aged 5-6 years with groups B1 totaling 10 people and B2 totaling 10 people. And for data analysis, normality, homogeneity, and hypothesis tests are used. The data collection tool is a statement sheet. Furthermore, the data were processed using hypothesis testing (t-test) using SPSS 19.0. Then based on the hypothesis test using the Independent sample t-test, the sig value (2-tailed) is 0.001 <0.05, it can be said that H1 is accepted and H0 is rejected. Thus it can be concluded that powerpoint-based educational games have an effect on children's math skills at Raudhatul Athfal Al-Ikhlas Darma Wanita Kemenag West Pasaman.